2008
DOI: 10.1007/s00292-008-1080-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression des „activated leukocyte cell adhesion molecule“ im Mammakarzinom

Abstract: Das invasive Karzinom der Brustdrü-se ist in den meisten Industrielän-dern die zweithäufigste Todesursache der Frau [1]. Eine Senkung der Mortalitätsrate wird über einen wachsenden Aufwand der Früherkennung und durch Verbesserung der postchirurgischen Therapie angestrebt. Die Modalität der postchirurgischen Therapie ist in hohem Maß vom pathologischen Befund mit Abschätzung der Aggressivität des Karzinoms durch die Bestimmung des Tumortyps, des TNM-Stadiums (T: "tumor", N: "node", M: "metastasis") und des hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…With respect to breast cancer, multiple studies have examined ALCAM expression at the transcript and protein levels, using a variety of methods. There is an emerging consensus that low level ALCAM is a bad prognostic marker in breast cancer [23,24,27,41-44]. In the largest, and most recent study, Ihnen et al found that low ALCAM mRNA was associated with shorter disease free survival and duration of survival in hierarchical cluster analysis involving training and multiple validation cohorts of breast cancer patients [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to breast cancer, multiple studies have examined ALCAM expression at the transcript and protein levels, using a variety of methods. There is an emerging consensus that low level ALCAM is a bad prognostic marker in breast cancer [23,24,27,41-44]. In the largest, and most recent study, Ihnen et al found that low ALCAM mRNA was associated with shorter disease free survival and duration of survival in hierarchical cluster analysis involving training and multiple validation cohorts of breast cancer patients [44].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies showed that patients with the lowest level of ALCAM transcripts develop skeletal metastasis [24], that low ALCAM correlated with an aggressive tumor phenotype and significantly negative correlation between ALCAM expression and tumor diameter and grade [25]. More recently high-level ALCAM in breast cancer tissues has emerged as a predictor of good outcome among patients treated with tamoxifen [26] and adjuvant chemotherapy [27,28]. …”
Section: Introductionmentioning
confidence: 99%
“…This consensus is supported by observation that patients with the lowest level of ALCAM transcripts developed skeletal metastasis [29], that low ALCAM correlated with an aggressive tumor phenotype and significantly negative correlation between ALCAM expression and tumor diameter and grade [26]. Conversely, high ALCAM expression correlated positively with progesterone and estrogen receptor expression, better response and longer overall survival in patients treated with adjuvant chemotherapy [28, 30]. Most recently, an independent study has shown that low ALCAM mRNA expression in breast cancer tissue was associated with shorter disease free survival and duration of survival (OAS) in a cohort of 481 patients [31].…”
Section: Introductionmentioning
confidence: 90%